Radical Cystectomy Compared to Combined Modality Treatment for Muscle-Invasive Bladder Cancer: A Systematic Review and Meta-Analysis - Vashistha, Vishal; Wang, Hanzhang; Mazzone, Andrew; Liss, Michael A.; Svatek, Robert S.; Schleicher, Mary; Kaushik, Dharam (International journal of radiation oncology, biology, physics, 2017)
To perform a comprehensive comparison of overall survival (OS), disease-specific survival (DSS), progression-free survival (PFS), and treatment-related complications between radical cystectomy (RC) and combined modality treatment (CMT—radiation therapy, concurrent chemotherapy, and maximal transurethral resection of bladder tumor) in the setting of muscle-invasive bladder cancer. We searched 7 databases (PubMed, Scopus, EMBASE, Proquest, CINAHL, and ClinicalTrials.gov) for randomized, controlled trials and prospective and retrospective studies directly comparing RC with CMT from database inception to March 2016. We conducted meta-analyses evaluating OS, DSS, and PFS with hazard ratios (HRs) and 95% confidence intervals (CIs). Nineteen studies evaluating 12,380 subjects were selected. For the 8 studies encompassing 9554 subjects eligible for meta-analyses, we found no difference in OS at 5 years (HR 0.96, favoring CMT, 95% CI 0.72-1.29; P=.778) or 10 years (HR 1.02, favoring cystectomy, 95% CI 0.73-1.42; P=.905). No difference was observed in DSS at 5 years (HR 0.83, favoring radiation, 95% CI 0.54-1.28; P=.390) or 10 years (HR 1.17, favoring cystectomy, 95% CI 0.89-1.55; P=.264), or PFS at 10 years (HR 0.85, favoring CMT, 95% CI 0.43-1.67; P=.639). The cystectomy arms had higher rates of early major complications, whereas rates of minor complications were similar between the 2 treatments. Current meta-analysis reveals no differences in OS, DSS, or PFS between RC and CMT. Further randomized, controlled trials are necessary to identify the optimal treatment for specific patients.